KEBIJAKAN PENATAAN KAWASAN MASJID AGUNG JAWA TENGAH DAN MUSEUM PERKEMBANGAN ISLAM JAWA TENGAH - David Nur Fajar; Wiwik Nur Widayati; Puji Astuti (Journal of Politic and Government Studies, 2013)
In this study, researchers wanted to know how the government's efforts to develop the city ofSemarang in Central Java tour of the grand mosque and Museum of Islamic development inCentral Java. And the researchers also wanted to know how the arrangement of tourismpolicy efforts against street vendors Semarang City Government located in the tourist area oftheGreatMosqueofCentralJava.This type of research is a qualitative descriptive study using a type. This study analyzes howpolicy structuring the grand mosque and museum java java development of Islam.After an examination of the efforts and policies, the result of research that says that theprocess of policy development is good, although still lacking, and the stage of thedevelopment process and evaluation of tourism management of the Great Mosque of CentralJava and Central Java, Islamic Development Museum itself, and others are running with quitewell despite some problems arise and deviations from post-relocation arrangement touristarea.